Phosphorus fertilizer prepared from natural Burenkhaan phosphorite (Mongolia) by a mechanical activation. Issue 3 (3rd May 2016) - Minjigmaa, A.; Oyun-Erdene, G.; Zolzaya, Ts.; Davaabal, B.; Amgalan, J.; Temuujin, J.
Abstract: Phosphorus is one of the most important nutrients for plant growth. The main compounds containing phosphorus are natural phosphate minerals such as apatite. However, the solubility of apatite is low in the humic acid in soil. Therefore, phosphorus is applied as a fertilizer for plant growth. Generally, fluorapatite Ca5 (PO4 )3 F is used for the preparation of phosphorus fertilizer such as superphosphate. Mongolia is rich in phosphorus reserves which are distributed between two phosphate basins at Khuvsgul (4.5 billion tonnes) and Zavkhan (1.2 billion tonnes). However, preparation of phosphorus fertilizer from natural fluorapatite, by a wet chemical method raises health and ecological concerns. Therefore, we have mechanically treated phosphorite from the Burenkhaan deposit in order to prepare fertilizer by a dry method. Phosphate samples were milled in a vibratory ball mill for 15–120 min. Raw and milled samples were characterized by XRD, FTIR, particle size analyzer and SEM. The efficacy of mechanical activation was determined by solubility of milled phosphate in a 2% citric acid solution. Mechanical activation results in a threefold increase in solubility of phosphorus in citric acid solution to 18%. Such solubility is comparable with the superphosphate prepared by the wet chemical method.